FLASH Radiotherapy Using Single-Energy Proton PBS Transmission Beams for Hypofractionation Liver Cancer: Dose and Dose Rate Quantification - Wei, Shouyi; Lin, Haibo; Choi, J. Isabelle; Press, Robert H.; Lazarev, Stanislav; Kabarriti, Rafi; Hajj, Carla; Hasan, Shaakir; Chhabra, Arpit M.; Simone, Charles B.; Kang, Minglei (Frontiers in Oncology, 2022)
Purpose: To study the dose and dose rate of transmission proton PBS FLASH radiotherapy(RT) for hypofractionation liver cancer based on the parameters of a commercial system. Methods and Materials: An in-house treatment planning software was developed to perform intensity-modulated proton therapy(IMPT) FLASH RT planning. Single-energy transmission proton PBS plans of 4.5Gy×15 fractions were optimized for seven consecutive hepatocellular carcinoma patients, using 2 and 5 fields combined with 1) the minimum MU/spot chosen between 100-400, and minimum spot time(MST) of 2ms; 2) the minimum MU/spot of 100, and MST of 0.5ms, based upon considerations in target uniformities, OAR dose constraints and OAR FLASH dose rate coverage. The 3D average dose rate distribution was calculated. The dose metrics were characterized to evaluate the dose quality for the different combinations of field numbers and minimum spot times compared to that of conventional IMPT plans. Dose rate quality was evaluated using 40Gy/s volume coverage(V40Gy/s). Results: All plans achieved favorable and comparable target uniformities, and target uniformity improved as the number of fields increased. For OARs, no significant dose differences were observed between plans of different field numbers and the same MST. For plans using shorter MST and the same field numbers, better sparing was generally observed in most OARs and was statistically significant for chest wall. However, the FLASH dose rate coverage V40Gy/s was increased by 20% for 2-field plans compared to 5-field plans in most OARs with 2ms MST, which was less evident in the 0.5ms cases. For 2-field plans, dose metrics and V40Gy/s of select OARs have large variations due to the beam angle selection and variable distances to the targets. The transmission plans generally yielded inferior dosimetric quality to the conventional IMPT plans. Conclusion: This is the first attempt to assess liver FLASH planning and demonstrates it is challenging for hypofractionation with smaller fractional doses(4.5Gy/fraction). Using fewer fields can allow higher minimum MU/spot, resulting in higher OARs FLASH dose rate coverages while achieving similar plan quality compared to plans with more fields. Shorter MST can result in better plan quality and comparable or even better FLASH dose rate coverage.